Rhetoric of allegorical formation in Maqamat Ayed Al-Qarni - Salih Mala Aziz; Yahya Mahmoud Ahmed (Zanco Journal of Humanity Sciences)
This research is a rhetorical reading in the shrines of Ayed Al-Qarni, the contemporary Islamic writer. The research consists of an introduction, two axes, an appendix and results. His literature and his statement in the service of preaching and spreading Islam, and the first axis is devoted to talking about declarative metaphors, starting by defining them in rhetorical blogs and showing their graphic value, Then we entered into analyzing models of the prophetic standing, the mandatory residency, the standardization of unification, and the modern residency to extract what is in it from metaphor not only by referring to metaphoric depiction, but also the general constructive analysis of the linguistic context in order to clarify its rhetorical dimensions, some of which are taken with the necks of some in achieving the coherence and interconnection of the text even Literary photography is more effective and more suggestive.In the wake of the first axis, we started with the second axis, which we made restricted to spatial metaphor, walking on the same approach that we took in analyzing declarative metaphors, so we took evidence from the prophetic standing, cosmic residency, beauty residency, and scientific residency, and we dealt with rhetorical analysis of what expanded the field and found the pen, In the meantime, we have referred to some of the characteristics of the metaphor of filtering, stripping, and launching, and to some of its advantages of diagnosis and embodiment, whether it came in the context of talking about the beauty of nature and its paintings or what came in the context of talking about spirits and abstracts, and the search ended with an appendix investigating what was mentioned Of the metaphors of all kinds in the shrines of Ayed Al-Qarni, the conclusion came to summarize the most important findings of the research.